Academic detailing in oral healthcare – results of the ADVOCATE Field Studies. (2nd October 2020) - Baâdoudi, Fatiha; Duijster, Denise; Maskrey, Neal; Ali, Fatima M.; Rosing, Kasper; van der Heijden, Geert J. M. G.
Abstract: Background: Academic detailing (AD) is a defined form of educational outreach that can be used to influence decision making and reduce unwarranted variation in healthcare delivery. This paper describes the results of the proof of concept phase of the ADVOCATE Field Studies. This study evaluated the feasibility, acceptability and usefulness of AD reinforced with feedback data, to promote prevention-oriented, patient-centred and evidence-based oral healthcare delivery by general dental practitioners (GDPs). Methods: In the Field Studies, six groups of GDPs ( n  = 39) were recruited in The Netherlands, Germany and Denmark. Each group had four meetings reinforced with feedback data for open discussions on dental practice and healthcare delivery. Conventional and directed content analysis was used to analyze the qualitative data collected from focus group interviews, debriefing interviews, field notes and evaluation forms. Results: A total of nine themes were identified. Seven themes related to the process of the Field Studies and covered experiences, barriers and facilitators to AD group meetings, data collection and the use of an electronic dashboard for data presentation and storage. Two themes related to the outcomes of the study, describing how GDPs perceived they made changes to their clinical practice as a result of the Field Studies. Conclusions: The ADVOCATE Field Studies approach offers a novel way of collecting and providing feedback to care providers which has the potential to reduce variation oral healthcare delivery. AD plus feedback data is a useful, feasible approach which creates awareness and gives insight into care delivery processes. Some logistic and technical barriers to adoption were identified, which if resolved would further improve the approach and likely increase the acceptability amongst GDPs.